PENGARUH PERHATIAN ORANG TUA DAN KONSEP DIRI SISWA TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Handayani, Dian (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2017)
Abstract: This research is an associative quantitative research that aims to determine the influence ofparents' attention, self-concept of students to the results of learning mathematics. This research wasconducted at SDN Wilayah Binaan Duren Sawit, Jakarta Timur. Samples were taken using ClusterRandom Sampling Technique, there were 120 students of class VI who were involved in the research.The timing of the research in the second semester of the academic year 2016/2017. The method usedin this research is survey method with path analysis. The instrument of data collection through the testof mathematics learning result and questionnaire has been tested its validity and reliability, thenanalyzed to prove hypothesis. Based on the results of the analysis found that: 1) a positive directinfluence between the attention of parents to student's mathematics learning outcomes; 2) there is apositive direct influence between self-concept to the student's mathematics learning outcomes; 3)there is a direct positive influence between the attention of parents to student self-concept. Theimplications of this research indicate that the aspect of parents' attention and self-concept of studentscan be used as an alternative to improve the achievement of mathematics learning result of elementaryschool students. Keyword: Results of mathematics learning, Parental attention and Student self-concept Abstrak, Penelitian ini adalah penelitian kuantitatif asosiatif yang bertujuan untuk mengetahuipengaruh perhatian orang tua, konsep diri siswa terhadap hasil belajar matematika. Penelitian inidilaksanakan di SDN Wilayah binaan Kelurahan Duren Sawit, Jakarta Timur.Sampel diambil denganmenggunakan Teknik Cluster Random Sampling, terdapat 120 siswa kelas VI yang dilibatkan dalampenelitian.Waktu pelaksanaan penelitian pada semester 2 tahun pelajaran 2016/2017.Metode yangdigunakan dalam penelitian ini adalah metode survei dengan analisis jalur (path analysis).Instrumenpengumpulan data melalui tes hasil belajar matematika dan kuesioner telah diuji validitas danreliabilitasnya, kemudian dianalisis untuk membuktikan hipotesis.Berdasarkan hasil analisis didapatbahwa: 1) adanya pengaruh langsung positif antara perhatian orang tua terhadap hasil belajarmatematika siswa; 2) adanya pengaruh langsung positif antara konsep diri terhadap hasil belajarmatematika siswa; 3) adanya pengaruh langsung positif antara perhatian orang tua terhadap konsepdiri siswa.Implikasi penelitian ini menunjukkan bahwa aspek perhatian orang tua dan konsep dirisiswa dapat dijadikan sebagai salah satu alternatif untuk meningkatkan capaiannya hasil belajarmatematika siswa sekolah dasar. Kata kunci :Hasil belajar matematika, Perhatian orang tua dan Konsep diri siswa